2021
DOI: 10.3389/fcomm.2021.729818
|View full text |Cite
|
Sign up to set email alerts
|

Twitter’s Fake News Discourses Around Climate Change and Global Warming

Abstract: In this empirical study, we collected about 6.8 million tweets that mentioned “fake news”, and we extracted references to climate change and/or global warming to understand the public discourses around these two issues. Using a mixed method, the study’s findings show that there is a clear politically polarized discussion on climate change. We found that the majority of tweets focus on the United States context though references to other Western coutnries are often made. The anti-Liberal or anti-Democratic onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…At the same time, the phenomenon of the widespread dissemination of false and misleading information is being observed, with social media being the most appropriate channel for its production and its rapid and widespread dissemination (Allcott & Gentzkow, 2017;Zimmer, et al, 2019;Avram, et al, 2020;Kouzy, et al, 2020;Li, et al, 2020;Ofcom, 2020;Pennycook, et al, 2020). Among the issues that vary in terms of their subject matter, the presence of misinformation is also found in general science-related issues (Allgaier, 2019;Landrum, et al, 2019;Cox, 2019;Al-Rawi, et al, 2021), as well as, in particular, the science of medicine (Kata, 2010;Buchanan & Beckett, 2014;Tonsaker, et al, 2014;Arseniev-Kohler, et al, 2016;Biggs, et al, 2013;Gage-Bouchard, et al, 2017;Blankenship, et al, 2018;Bora, et al, 2018;Cavazos-Rehg, et al, 2018;Gu & Hong, 2019;Brennen, et al, 2020;Gao, et al, 2020;Kouzy, et al, 2020;Li, et al, 2020;Pennycook, et al, 2020;WHO, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the phenomenon of the widespread dissemination of false and misleading information is being observed, with social media being the most appropriate channel for its production and its rapid and widespread dissemination (Allcott & Gentzkow, 2017;Zimmer, et al, 2019;Avram, et al, 2020;Kouzy, et al, 2020;Li, et al, 2020;Ofcom, 2020;Pennycook, et al, 2020). Among the issues that vary in terms of their subject matter, the presence of misinformation is also found in general science-related issues (Allgaier, 2019;Landrum, et al, 2019;Cox, 2019;Al-Rawi, et al, 2021), as well as, in particular, the science of medicine (Kata, 2010;Buchanan & Beckett, 2014;Tonsaker, et al, 2014;Arseniev-Kohler, et al, 2016;Biggs, et al, 2013;Gage-Bouchard, et al, 2017;Blankenship, et al, 2018;Bora, et al, 2018;Cavazos-Rehg, et al, 2018;Gu & Hong, 2019;Brennen, et al, 2020;Gao, et al, 2020;Kouzy, et al, 2020;Li, et al, 2020;Pennycook, et al, 2020;WHO, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is potential bias with social media users because of the characteristics of country, region, age, and so on. In addition, the contents of Twitter, Facebook, Instagram, Flickr, and YouTube often include falsehoods and ethical issues (i.e., hate claims, and slander and libel against specific individuals or groups) (Al-Rawi et al, 2021;Albahli, 2022;Leahy et al, 2022;Toliyat et al, 2022;Wang et al, 2022). They also are limited and contain uncertainty caused by a lack of clarity in the terms of use for data and copyright, and Twitter, Facebook, and YouTube lack exact geolocation information unlike Instagram and Flickr (Shin et al, 2021;2024a).…”
Section: Social Sensingmentioning
confidence: 99%
“…A study that examined the period around the time of former USA President Donald Trump's announcement of the country's withdrawal from the Paris Agreement, in 2017, found that suspected bots in Twitter conversations were more frequent in some topic areas than others, including denialist discourse (Marlow et al 2021). Another work found that, on Twitter, discussions on 'global warming' (preferred expression between conservatives) are heavily influenced by automated accounts, unlike 'climate change' (preferred expression between liberals), in which the majority of the top users appear to actually be humans (Al-Rawi et al 2021). With a dataset queried in English at the time of United Nations Climate Change Conference in 2018 (COP24), another study found that, in Twitter networks of both climate contrarians and climate accepters, botlike accounts were equally active (Tyagi et al 2020).…”
Section: Social Bots and The Environmental Debatementioning
confidence: 99%